Fighting Landlessness: Women Farmers' Resistance in an Exclusive Agrarian Structure - Syaifudin Suhri Kasim; Aryuni Salpiana Jabar; Ratna Supiyah; Sarpin; Rosdiana (CV. Literasi Indonesia, 2026)
Gender-based agrarian inequality remains a structural constraint that limits women farmers’ access to resources and recognition of their labor, particularly among landless women. This study examines how landless women farmers understand agrarian exclusion and develop resistance within unequal rural agrarian structures. Using a critical qualitative approach with an ethnographic–narrative case study design, the research involved ten landless women engaged in agricultural and rural livelihood activities. Data were collected through in-depth interviews, participant observation, document analysis, and thematic analysis. The findings show that the absence of formal land ownership does not negate women’s agency. Instead, women interpret agrarian inequality as a structural issue and respond through contextual, everyday resistance practices. These include strategic management of agrarian labor, mobilization of community-based social capital, use of local knowledge, and the rearticulation of identity from invisible farm laborers to household livelihood managers. This study contributes to feminist agrarian scholarship by foregrounding women’s agency and challenges dominant narratives that frame landless women farmers as merely passive and vulnerable, underscoring the need for gender-responsive agrarian and rural development policies.